Analisis Implementasi Program Bulan Imunisasi Anak Sekolah Di Puskesmas Sidomulyo Kota Pekanbaru - Anggi Wahyuni; Kiswanto Kiswanto; Jasrida Yunita; Budi Hartono; Dedi Widodo; Asfeni Asfeni (Universitas Hang Tuah Pekanbaru, 2025)
The School Children Immunization Month program aims to protect children against Immunization-Preventable Diseases until school age. In percentage terms, BIAS achievement is far from the target, with the highest immunization coverage of only around 18% Measless Rubella, and the lowest 6.3% Diphterie Tetanus 2. Sidomulyo Community Health Center and it was the lowest coverage in the city. The success of the BIAS program policy implementation is influenced by various interrelated factors. This study aims to analyze the implementation of the School Children Immunization Month Program at the Sidomulyo Community Health Center in Pekanbaru City in 2025. This qualitative study was conducted in July 2025 with 14 informants. Research variables include communication, resources, implementer attitudes, bureaucratic structure, environment, and policy standards and targets. The results show that communication is not optimal even though the program is running, good technical implementation is supported by adequate facilities and professional staff, and the attitudes of officers influence parental trust. The program involves the Community Health Center, Health Office, Education Office, schools, and community leaders, but participation is still low due to religious, social, cultural, and hoax factors. Despite clear SOPs, vaccination targets have not been achieved for the past three years. It is recommended to improve interactive communication strategies, strengthen education and cross-sector coordination, and map areas for evaluation and improvement of program implementation.